PENERAPAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS VII1DI MTs MUHAMMADIYAH LUBUK JAMBI - Mariyani Oktaviya; Andrizal Andrizal; Helbi Akbar (Universitas Islam Kuantan Singingi, 2020)
In following the learning process sometimes students get bored, the solution to overcome students boredom in the learning process is a way implement an attractive and fun learning model of students, one of them is applying the Numbered Head Together learning (NHT). Based on the results of data collection by means of observation, tests, interviews and documentation, then analyzed the data using graphs concluded that: the application of the Numbered Head Together (NHT) can improve the learning outcomes of class VII1 students in the field of Islamic civilization History at MTs Muhammadiyah Lubuk Jambi, this is proven by the increase pre-cycle to cycle all III with a percentage of 69,18 (pre-cycle), 76,14 (cycle I), 80,43 (cycle II) and 89,54 (cycle III). So the learning outcomes of grade VII1 students at MTs Muhammadiyah Lubuk Jambi continue to increase according to the results of the evaluation. The factors that affect the learning outcomes of the field of Islamic Civilization students at MTs Muhammadiyah Lubuk Jambi based on observations are: 1) lack of strategies and techniques in learning the Fiqih applied by the teachers, 2) the ability of students in language so as to answering questions having difficulty speaking, 3) students’ abilities who do not speach without concept, this can be seen when the discussion held students do not comment, 4) the lack of students involved in the learning process so that learning is centered on the teacher.